Modeling of Underground Heat Exchanger for Heat Pump and Air Conditioning Systems - Sarwo Edhy S (Jurnal Teknik Mesin Unsyiah, 2012)
Air conditioning and heat pump systems can use the ground as a medium to dump or absorb heat energy to increase efficiencies. As compared to the air, the ground has lower temperature in the summer and higher in the winter. In this research, the vertical U tube underground heat exchanger that can be used to harvest geothermal energy, has been modeled by using two dimensional finite difference methods. The model is not only able to estimate the water temperatures out of vertical U tube underground heat exchanger, but also capable of calculating the temperature profile change of surrounding soil under various water entering heat exchanger and weather conditions. The heat transfer process between the underground heat exchanger and soil has been investigated and profiles of soil and water temperatures are presented.